The characteristics of the gut microbiota in patients with Kawasaki disease: a systematic review - Chen, Hongbo; Liu, Hanmin; Qiao, Lina; Liu, Yang; Yu, Dan; Wang, Zhiling; Wang, Tao; Li, Weiran (Frontiers in Microbiology, 2025)
The gut-vascular axis has emerged as a critical focus of research, with accumulating evidence suggesting distinct alterations in intestinal microbiota among patients with Kawasaki disease (KD). However, no systematic review to date has comprehensively characterized gut microbial dysbiosis in this population. This systematic review aimed to investigate changes in the composition of gut microbiota in KD patients. A comprehensive search of MEDLINE, EMBASE, Web of Science, and the Cochrane Library databases was conducted, and the study quality was assessed using the Newcastle-Ottawa Scale. All reported taxa were re-annotated according to the SILVA 138 database. Seven studies were enrolled in our review. In acute-phase KD, reduced α-diversity and significant β-diversity divergence were observed compared to healthy controls (HCs). Concurrently, taxa with potential short-chain fatty acid (SCFA)-linked protective functions showed diminished abundance, including Bacteroidota, Bacteroides, Roseburia, Faecalibacterium, Blautia, Dialister, Lachnospira, and Prevotella, while opportunistic pathogens such as Enterococcus were enriched in acute-phase KD cohorts. For non-acute KD patients, β-diversity remained distinct, with reduced abundance of the SCFA-producing genus Blautia. These findings suggest that gut microbiota dysbiosis may be associated with KD pathogenesis via immunomodulatory pathways, although the mechanistic insights remain to be elucidated.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251148103